Kompleks Islam Putrajaya (KIP), Wilayah Persekutuan - Mohd Shah, Asyraaf Hakimi; Shahrin, Shazarul Akma; Ahmad Puzi, Muhammad Fahmi Izuddin (2024)
This report is an interpretation of all of the actions that we learned and saw during our trip to our case study at Kompleks Islam Putrajaya (KIP) in Wilayah Persekutuan. This study covers the topics that we have learned over the semesters, with a focus on the management, operation, and financial upkeep of this building by the facility management team of TH Universal Builders Sdn Bhd. This report's content is based on the requirements, and all information and data are gathered to complete all of the required chapters. According to the requirements, it must include the detailed study of the property, the maintenance management organization, the maintenance policy and planning, the building design and structural design, the building condition assessment, the maintenance strategy, the legal aspect, the financial aspect, the problem and the recommendation. The report will conclude with the overall study's conclusion. All of the writing on analysis, explanation, and classification is from the perspective of us Diploma in Building Surveying students. The information supplied comes from the maintenance department, the internet, and our observations of the Kompleks Islam Putrajaya (KIP). Maintenance management is regarded as an essential component of any building in order to ensure that the quality of any aspect related to the building is preserved in the best condition, to extend the building's life cycle, to minimize inconvenience, and to provide comfort, safety, and security for tenants and users.